Effects of Shenmai injection against chronic heart failure: a meta-analysis and systematic review of preclinical and clinical studies - Wu, Yang; Li, Tianli; Li, Pochen; Peng, HsuanChieh; Gao, Ang; Wang, Jisheng; Zhu, Haiyan; Wang, Xian (Frontiers in Pharmacology, 2024)
Objective: This study aims to evaluate the clinical and preclinical efficacy of SMI in treating CHF, and to summarize the relevant mechanisms of action in order to provide evidence for its role in CHF treatment.A systematic computerized search of eight databases and three registry systems was performed, with the time frame spanning from the inception of the databases to June 30, 2023. Strict procedures were used for data extraction, quality assessment, and data analysis. The methodological quality of the included studies was assessed using RoB-2 and SYRCLE tools. Statistical analysis was performed using Rev Man 5.4 software, using either fixed-effects or random-effects models.: A total of 25 clinical trials (including test group 1,367 patients, control group 1,338 patients) and 11 animal studies (including 201 animals) were included in this review. The metaanalysis of clinical studies showed that SMI can improve cardiac function indicators (LVEF, LVFS, LVEDV, LVESV, LVEDD, LVESD) (P<0.00001), reduce BNP/NT-proBNP levels (P<0.01), and improve inflammatory markers (hs-CRP, TNF-α, IL-6) (P<0.00001) and endothelin (ET) levels (P<0.0001). In animal studies, SMI demonstrated improved cardiac function (LVEF, LVFS) (P<0.05), and improved heart failure markers (NT-proBNP, P<0.05) when compared to control groups.Conclusions: This study represents the first meta-analysis which includes both preclinical and clinical studies on SMI. Clinical and animal studies have shown that SMI can improve cardiac function in CHF patients through its anti-apoptotic effects, antioxidant activities, anti-inflammatory effects, and improvement of myocardial metabolism. This study has certain limitations in terms of literature quality, quantity, and follow-up time. Therefore, the conclusions drawn from this study may require further validation through larger-scale, high-quality RCT trials.